2011
DOI: 10.3109/14767058.2011.622011
|View full text |Cite
|
Sign up to set email alerts
|

Early perinatal diagnosis of mothers at risk of developing post-partum depression – a concise guide for obstetricians, midwives, neonatologists and paediatricians

Abstract: We hope to provide those clinicians who are engaged in the care of pregnant women and their children with a valuable and user-friendly instrument for understanding and making a timely diagnoses of at-risk psychopathological phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
3
0
1
Order By: Relevance
“…In former studies [48][49][50] we hypothesized that women with a particular values constellation referred to in psychopathological literature as typus melancholicus (TM), experience motherhood as a social duty to perform in conformity to the dictates of tradition and that the adoption of this attitude is likely to turn motherhood into a traumatic event. TM is a personality type which is more likely to develop major depression (melancholia) .…”
Section: Motherhood As Diseasementioning
confidence: 99%
“…In former studies [48][49][50] we hypothesized that women with a particular values constellation referred to in psychopathological literature as typus melancholicus (TM), experience motherhood as a social duty to perform in conformity to the dictates of tradition and that the adoption of this attitude is likely to turn motherhood into a traumatic event. TM is a personality type which is more likely to develop major depression (melancholia) .…”
Section: Motherhood As Diseasementioning
confidence: 99%
“…They do all they can in planning how not to neglect their duties as a mother, wife, and worker. These duties cannot be delegated to others without experiencing guilt or feelings of being a “bad mother,” paving the way for falling into a depressive condition [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intolerance of uncertainty may create a negative bias in the individual's thinking, lead to rumination and impair the ability to solve problems and deal with ambiguous and distressing situations (Greco & Roger, 2003 ). Furthermore, more intolerance of uncertainty has been related to more dysfunctional maternal behaviours in the postpartum period (Ambrosini et al, 2012 ). However, although intolerance of uncertainty has been associated with anxiety disorders (Boswell et al, 2013 ), which were found to contribute to a greater perception of infant invasiveness (Davies et al, 2008 ; Lefkovics et al, 2018 ), to the best of our knowledge, no previous studies have examined the relationship between intolerance of uncertainty and parents' perceptions of the infant.…”
Section: Introductionmentioning
confidence: 99%